The correlation of the interhamular notch width and its antero-posterior distance to the palatine fovea of edentulous maxillary arches - Basaya, Joanna K.; Javier, Janice A.; Atienza, Charleton (Adviser).
In complete denture making of the maxillary arch, positioning the posterior palatal border is of utmost importance for retention and stability. The posterior border is placed on the vibrating line, which is 2 mm. anterior to the palatine fovea if the mechanical method is used. However, there are instances where the palatine fovea is not present nor copied during final impression making and so this becomes a problem to the clinician. The aim of this study was to determine the correlation of the inter-hamular notch width and its antero-posterior distance to the palatine fovea of edentulous maxillary arches. This is to predict the position of the palatine fovea and consequently the vibrating line. Forty-nine master casts of patients with edentulous maxillary arches fabricated by UPCD clinicians in the UPCD Prosthodontics Section from September to December 2000 were examined for their inter-hamular notch width, their antero-posterior distance to the palatine fovea and palatal configuration. The age and sex were noted. The variables were subjected to correlational analysis, t-test and Kruskal-Wallis test. The researchers concluded that there is a weak inverse relationship between the inter-hamular notch width and its antero-posterior distance to the palatine fovea of edentulous maxillary arches of Filipino UPCD patients regardless of age, sex and palatal configuration.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Edentulous mouth; Complete dentures